(untitled) (UNIZIK Journal of Marketing, 2024)
The rising magnitude of criminal activities at the community level despite the enormous amount allocated to security in successive National and State budgets is the major factor that triggered this study. The huge resources expended on the military, Nigerian police force and other law enforcement agencies in the country appears not to have yielded the desired results as the wave of crimes have continued to rise. This study examines how community engagement and perception influence neighborhood crime prevention. The study adopted descriptive survey while data was collected from sampled respondents through questionnaire. The population of the study comprised rural dwellers resident in ten (10) communities in Ado local government area of Ekiti state, Nigeria. Simple random sampling was used to select five (5) out of the ten (10) communities while purposive sampling technique was used to select 100 respondents from each community. In all, a total of 500 participants were selected. Data collected was processed and analysed using simple linear regressions. Results of the investigation revealed that the four (4) proxies of community relations strategies have positive and significant effects on neighborhood crimes prevention and have the potential of sustaining national security in Nigeria. It was recommended that local governments should establish community policing frameworks and provide regular public education campaign on crime prevention.